Defects and Reliability of GaN‐Based LEDs: Review and Perspectives. Issue 8 (24th February 2022) - Buffolo, Matteo; Caria, Alessandro; Piva, Francesco; Roccato, Nicola; Casu, Claudia; De Santi, Carlo; Trivellin, Nicola; Meneghesso, Gaudenzio; Zanoni, Enrico; Meneghini, Matteo
Abstract : Herein, the main factors and mechanisms that limit the reliability of gallium nitride (GaN)‐based light‐emitting diodes (LEDs) are reviewed. An overview of the defects characterization techniques most relevant for wide‐bandgap diodes is provided first. Then, by introducing a catalogue of traps and deep levels in GaN and computer‐aided simulations, it is shown which types of defects are more detrimental for the radiative efficiency of the devices. Gradual degradation mechanisms are analyzed in terms of their specific driving force: a separate analysis of recombination‐enhanced processes, driven by nonradiative recombination and/or temperature‐assisted processes, such as defects or impurity diffusion, is presented. The most common lifetime estimation methods and standards adopted for solid‐state luminaires are also reported on. Finally, the paper concludes by examining which are the typical degradation and failure mechanisms exhibited by LEDs submitted to electrical overstress. Abstract : This article provides an overview of the main factors and mechanisms that limit the short‐ and long‐term reliability of modern GaN‐based light‐emitting diodes. Relevant defects, and related characterization techniques, for III‐N materials are analyzed, and their impact on device performance is evaluated.